L’avenir des ressources génétiques marines au-delà des juridictions nationales : enjeux à l’aube d’un nouveau traité international - Nathan Brison; Christine Frison (VertigO)
Over the last decades, the pressure on the environment of marine areas beyond the national jurisdiction of States (ABNJ) has been steadily increasing. In addition to the already visible impact of activities such as deep-sea fishing and maritime traffic, the future development of several other activities, particularly the exploitation of gas, oil, mineral resources and genetic resources, raises fears of potential serious damage to the environment of ABNJ. For this reason, on December 24, 2017, the United Nations General Assembly (UNGA) opened negotiations on a new treaty for the conservation and sustainable use of marine biodiversity of the ABNJ. Three years later, many observers of these negotiations are questioning the future of the oceans, pointing to the environmental urgency in the face of the lack of ambition of the negotiated text. In this article, we conduct a legal analysis of the treaty under negotiation, and more specifically of the regime on access to marine genetic resources and benefit sharing, in order to demonstrate that it offers a new illustration of a recurring dilemma in environmental negotiations: finding the right balance between adopting standards that are too unambitious to achieve conservation objectives, or too ambitious to ensure States’ support. Yet, when it comes to biodiversity conservation, the balance of economic and environmental interests has very often tilted in the former direction. We argue that this cursor could be moved through the governance of ABNJ as a global commons. Such a comprehensive, cross-sectoral, integrated and multidisciplinary vision would not only work towards better conservation of marine biodiversity, but also towards benefit sharing, capacity building and transfer of more environmentally friendly techniques. The global health crisis that began in 2020 demonstrates the urgency of a paradigm shift and a reconceptualization of our relationship to biodiversity. Faced with the limits of the traditional reactive strategy, we advocate for a systemic upstream action, which implies rethinking the way we manage, use, and value natural resources, as well as putting biodiversity and ecosystems back at the heart of our societies. It is in this new dynamic that the negotiations for an agreement on ABNJ should continue in August 2021, in order to preserve the true wealth of our oceans.